A CRISPR/Cas9-Based Mutagenesis Protocol for Brachypodium distachyon and Its Allopolyploid Relative, Brachypodium hybridum - Hus, Karolina; Betekhtin, Alexander; Pinski, Artur; Rojek-Jelonek, Magdalena; Grzebelus, Ewa; Nibau, Candida; Gao, Mingjun; Jaeger, Katja E.; Jenkins, Glyn; Doonan, John H.; Hasterok, Robert (Frontiers in Plant Science, 2020)
The CRISPR/Cas9 system enables precise genome editing and is a useful tool for functional genomic studies. Here we report a detailed protocol for targeted genome editing in the model grass Brachypodium distachyon and its allotetraploid relative B. hybridum, describing gRNA design, a transient protoplast assay to test gRNA efficiency, Agrobacterium¬-mediated transformation and the selection and analysis of regenerated plants. We targeted the gene encoding phytoene desaturase (PDS), which is a crucial enzyme in the chlorophyll biosynthesis pathway. The albino phenotype of mutants obtained confirmed the effectiveness of the protocol in functional gene analysis. Additionally, we targeted two genes related to cell wall maintenance, encoding a fasciclin-like arabinogalactan protein (FLA) and a pectin methylesterase (PME), and two genes encoding cyclin-dependent kinases (CDKG1 and CDKG2) which may be involved in DNA recombination. Cas9 activity induces mainly insertions or deletions, resulting in frameshift mutations that, may lead to premature stop codons. Because of the close phylogenetic relationship between Brachypodium species and key temperate cereals and forage grasses, this protocol should be easily adapted to target genes underpinning agronomically important traits.